INCREASING MOTHER'S KNOWLEDGE ABOUT COMPLEMENTARY FOOD (MP-ASI) IN POLENGAN VILLAGE, MAGELANG DISTRICT - Nur Fitri Ayu Pertiwi; Yulia Sari; Aticeh Aticeh (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
This research is motivated by the need for counseling regarding nutritional fulfillment when giving MP-ASI in Polengan Village, Magelang Regency. This research is the first study conducted to assess changes in mothers' knowledge about nutrition during complementary feeding before and after being given counseling. A total of 30 subjects participated in this study (n = 30; 30 women). Data collection used a questionnaire regarding nutritional adequacy during the MP-ASI process. The results of the questionnaire showed an increase in knowledge of less than 23%, 71% good, and 6% good. After counseling about nutritional adequacy during MP-ASI there was an increase in knowledge of less to 0%, 18% sufficient, and 82% good. The results of this study indicate a good change in knowledge after being given counseling.